2017
DOI: 10.1002/ird.2170
|View full text |Cite
|
Sign up to set email alerts
|

Using Regional Virtual Water Trade and Water Footprint Accounting for Optimizing Crop Patterns to Mitigate Water Crises in Dry Regions

Abstract: The Qazvin Plain is one of the most important crop‐producing regions in Iran that are facing water shortage crises. Therefore, agricultural water management has been taken into consideration. In this study, water footprint (WF) accounting and virtual water (VW) trade were employed to determine the current condition of the plain's water resources. The total WF was obtained as 2050 MCM yr−1, of which green, blue, grey and white WF accounted for 31, 25, 2 and 42%, respectively. Having 44% of the total WF as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Reduction in precipitation and increasing daily minimum temperature, which could in turn result in lower chances of snowfall in winter, can significantly reduce domestic and agricultural water supplies in spring and summer. Given that nearly 65% of Iran's arable land was equipped with irrigation in 2014–2016 (Food and Agriculture Organization of the United Nations (FAO), ) and considering the already scarce and unstable status of groundwater in most of the plains in the country (Mojtabavi et al, ), this is expected to put more pressure on the country's agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in precipitation and increasing daily minimum temperature, which could in turn result in lower chances of snowfall in winter, can significantly reduce domestic and agricultural water supplies in spring and summer. Given that nearly 65% of Iran's arable land was equipped with irrigation in 2014–2016 (Food and Agriculture Organization of the United Nations (FAO), ) and considering the already scarce and unstable status of groundwater in most of the plains in the country (Mojtabavi et al, ), this is expected to put more pressure on the country's agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…More than 144 000 ha of land in this province is dedicated to wheat, as the most important crop in the region, which produces about 315 000 t yr − 1 . Also, maize is responsible for more than 11% of irrigated lands of the province, which results in 1008015 tons per year (Mojtabavi et al, 2018). In this study, both crops, wheat and maize, were investigated, but due to the similarity of the results, only one crop, wheat, was studied.…”
Section: Case Study and Field Datamentioning
confidence: 99%
“…Rehman et al [71] investigated the economic impact of major crops on the GDP of Pakistan and indicated that cotton, wheat, rice, and maize crops have a positive relationship with GDP while sugarcane crops have a negative effect. In another study, Mujtabai et al [72] recognized that stopping the exports of agriculture commodities is not a wise decision for the economic perspective of a country, so net benefits of alternative cropping patterns should be close to the current benefits. Aldaya et al [50] highlighted that 'more crop per drop' investigation should also consider economic aspects to achieve 'more cash per drop' at the same time.…”
Section: Conflicts Of Interestmentioning
confidence: 99%